Hubungan literasi informasi dengan self-directed learning mahasiswa Fakultas Ilmu Komunikasi - Maulida, Nisrina Zakiyah; Rizal, Edwin; Perdana, Fitri (Faculty of Communication, Padjadjaran University, 2024)
The creation of a thesis, which is the outcome of student research, is one of the requirements for graduation in higher education. In the thesis completion process, students are required to have adequate information literacy and self-directed learning skills. Students of Fikom Unpad, class of 2016, were introduced to the concept of information literacy during the new student orientation and in the TPB (Preparation Stage for Learning) program in the KBLI (Information Literacy Learning Activities) course. This research aims to identify the relationship between information literacy and self-directed learning among Fikom Unpad students of the 2016 class in the thesis preparation process. The research method used is quantitative, utilizing Chi-square and Pearson Product Moment analysis. The theoretical foundation refers to the ACRL (Association of College, Research, and Library) standards of 2000, covering aspects of information needs, information search strategies, information evaluation, information usage, and ethics and law in information use. This study involved 209 students of Fikom Unpad, class of 2016, with a sample size of 136 individuals. The results show a significant relationship between information literacy (X) and self-directed learning (Y), with a high correlation between sub-variable X (information needs, information search strategies, and information usage) and variable Y. Meanwhile, other sub-variables of X (information evaluation, ethics, and the law of information use) have a moderate relationship with variable Y. It was found that students' motivation and self-directed learning ability can increase with improved information literacy skills, considering the interrelation between the indicators of information literacy and self-directed learning. The higher the level of students' information literacy, the better their self-directed learning abilities.